Programa de dramatización “Asiri Warma” para disminuir las conductas agresivas en los niños de 5 años de la I.E. N° 215 en el año 2015 - Romero Hernández, Esthefany Lyzeth (2018)
The present thesis: DRAMA PROGRAM TO REDUCE ASIRI WARMA AGGRESSIVE BEHAVIOR IN CHILDREN UNDER 5 YEARS OF THE IE No. 215 in 2015, whose main aim to meet the individual needs of children, directly generating self-esteem and self-discipline , and indirectly kindness and courtesy, achieving a good and adequate social coexistence._x000D_ This thesis was based on the highest manifestation of aggressive behavior that showed children 5 years of the initial level of the IE No. 215, on the study sample 52 children, with 26 children in blue and turquoise classroom classroom 26 children._x000D_ Research is quasi-experimental with the application of a pre and post test, and the blue group and the experimental classroom classroom turquoise control group._x000D_ The dramatization program was applied to reduce aggressive behaviors in the experimental group, the results obtained in the pretest 61.5% showed high aggressiveness and in the post test a decrease of 7.7% was observed in the experimental group, which have shown that the students of this group, managed to significantly reduce the degree of aggressiveness.